Pengaruh Lower Limb Tension Test Terhadap Penurunan Nyeri Terhadap Nyeri Punggung Bawah di RSUD KRMT Wongsonegoro - Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2022)
Background: Lower back pain (NPB) Ischialgia is a pinched ischialgia nerve in the lower back area which causes the buttocks, thighs, lower legs and even feet to become tingling, painful, and sometimes causing weakness. Nerve mobilization is a manipulation technique by moving and stretching nerve tissue to increase axonal transportation so that it can improve nerve conduction. Nerve mobilization can reduce the pressure in the nerves so that there is an increase in blood flow to the nerves, which can have a regenerative and healing effect on injured nerves (Butler, 1991). Nerve mobilization is often used as a form of diagnosis and treatment for musculoskeletal conditions with nerve involvement (Butler, 1991). Nerve mobilization in the Lower Limb Tension Test (LLTT) is carried out at the branches of the Brachial plexus such as the radial nerve, median nerve and ulnar nerve. But here the author only discusses LLTT in the ishiadic nerve, namely LLTT 1 which is related to lower back pain. The aim is to determine physiotherapy management and the effect of Ultrasoundtherapy therapy and nerve mobilization using the LLTT 1 method in cases of lower back pain on reducing pain and increasing the functional ability of the hand. Two group pre test and post test method. RESEARCH PLACE: Physiotherapy clinic, RSU Sidoarjo. TIME: Measuring instrument: Visual Analouge Scale (VAS). Results: treatment using the Mann-Whtney test. With confidence interval (CI) (95%) The results of the study revealed that there was a significant difference in pain in group 1 (p = 0.00) and group 2 (p = 0.00). But there was no significant difference between the two groups in pain improvement (p = 0.152), so there was no better treatment between the two groups. Conclusion: It is concluded that ULTT is useful in treating CTS patients to reduce pain in two groups. The targeted outcomes are publications in national journals indexed by Sinta and HAKI. The TKT target for implementing this gamelan accompaniment exercise is level 2.